Analysis of Lexical Meaning of Verbs in the Translation of the Article “Media Digitalization and Political Communication” in NADI Magazine Edition 28/2021 - Muhammad Azmi Fahreza; Tanti Kurnia Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to describe how the analysis of the lexical meaning of verbs in the translation of the article Digitalization of Media and Political Communication in NADI Magazine Edition 28/2021. This study uses a qualitative descriptive method to analyze the lexical meaning of verbs in Indonesian and German translations. Data were taken from the article